Cluster Business Development Model of Agribusiness-Based MSMEs During the COVID-19 Pandemic - Mariyudi Mariyudi; Ikramuddin Ikramuddin; Khairil Anwar; Faisal Matriadi (Journal Research of Social Science, Economics, and Management, 2022)
Currently in Indonesia, Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the development of the national economy. This study aims to develop an integrated framework that incorporates the innovation and strategic sustainability behaviors into the cluster business development model of agribusiness-based MSMEs during the COVID-19 pandemic. This study uses mixed methods with quantitative and qualitative approaches. The subjects in this study were 150 members of the center member entrepreneurs, managers of the Regional Innovation System (SIDa), cooperative administrators/managers, related agencies, universities and other parties involved in the implementation of the SIDa program, and MSMEs business development. The results of the analysis using the radar scale and scoring analysis show that there are twelve potentials and economic opportunities for MSMEs business spread over three zones. The results of the mapping using the value-added matrix found that most of the MSME business characteristics had a "none" or "simple" value. This study also found developing an integrated framework that incorporates the innovation and strategic sustainability behaviors into the cluster business development model of agribusiness-based MSMEs during the COVID-19 pandemic. The main theoretical contribution of this paper is that this study proposes a model that explains how the different elements of strategic sustainability behavior and innovation types that focus on the cluster business into the model affect the business performance, business sustainability, and business survival of the cluster business of agribusiness-based MSMEs during the COVID-19 pandemic.